Pelatihan Penggunaan E-Library Di SMP Negeri 13 Jayapura - Rahman, Rahman; Sampebua, Mingsep Rante; Tanjung, Rosye H. R (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Public junior high school 13 Jayapura did not implement the e-library application in the library, causing difficulties in book management, book borrowing transactions, and students needing assistance to find books in the library. The purpose of this community service activity is to apply science and technology through training in using web-based e-library applications to students of Jayapura 13 public junior high school. Training activities increase students' knowledge, skills, and interest in reading. Implementation of activities includes lectures, discussions, questions and answers, demonstrations, practice, and evaluation. The implementation of this community service activity consists of six stages, namely coordination with the school, socialization of the use of the e-library application, training and practice of using the e-library application, evaluation, and preparing reports. The results of this community service activity are that students can operate the e-library application, increase their knowledge and skills in using the e-library application, make it easier to find books in the library and increase their interest in reading through the e-library application.